The port-bureaucratic organization: new perspectives on organizational change - Heckscher, Charles; Donnellon, Anne (California: Sage Publications, Inc, 1994)
Contents: 1. defining the port-bureaucratic type. 3. teams, performace, and rewords: will the post-bureaucratic organization be a post-merito creatic organization? 4. cognitive reapportion ment: reathinking the location of judement in managerial decision marking. 5. the virtual organization: bureaucracy, technology, and the huplosion of control. 6. transformational processes. 7. the paradox of control. 8. bureaucracy: can we do better? we can do worse
Keywords: Administración del Cambio